2020
DOI: 10.1111/1365-2745.13435
|View full text |Cite
|
Sign up to set email alerts
|

Drought legacies are short, prevail in dry conifer forests and depend on growth variability

Abstract: 1. The negative impacts of drought on forest growth and productivity last for several years generating legacies, although the factors that determine why such legacies vary across sites and tree species remain unclear. 2. We used an extensive network of tree-ring width (RWI, ring-width index) records of 16 tree species from 567 forests, and high-resolution climate and normalized difference vegetation index (NDVI) datasets across Spain during the common period 1982-2008 to test the hypothesis that climate condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 55 publications
(147 reference statements)
5
50
3
Order By: Relevance
“…How drought-induced growth reductions translate to changes in primary productivity and vegetation activity at the ecosystem level remains unclear (Gazol et al, 2020). Interestingly, we found a positive relationship between RWIstd and NDVI, which is in accordance with previous results (Vicente-Serrano et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…How drought-induced growth reductions translate to changes in primary productivity and vegetation activity at the ecosystem level remains unclear (Gazol et al, 2020). Interestingly, we found a positive relationship between RWIstd and NDVI, which is in accordance with previous results (Vicente-Serrano et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…According to our results the capacity to recover from drought of gymnosperms from dry sites is faster than that of angiosperms in general (Gazol et al, 2018). However, it is also true that most studies have found longer and more lasting legacies of drought in gymnosperms than in angiosperms (e.g., Anderegg et al, 2015;Gazol et al, 2020). Recently, DeSoto et al (2020) found that those trees that die because of drought presented lower growth resilience than surviving ones.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…For instance, evaluation of tree-ring growth during and after extreme weather events allows us to examine the stability of forest productivity and tree growth across different spatial and temporal scales (Cavin & Jump, 2017;Gazol et al, 2018;Lloret et al, 2011;Sánchez-Salguero, Camarero, Carrer, et al, 2017;Sánchez-Salguero et al, 2018). Furthermore, impacts of drought on tree growth can last for years, resulting in the so-called 'legacy effects' (Anderegg et al, 2015;Cavin et al, 2013;Gazol et al, 2020;Kannenberg et al, 2019;Peltier et al, 2016). These legacy effects increase as drought episodes become longer and occur closer in time (Peltier & Ogle, 2019).…”
Section: Introductionmentioning
confidence: 99%